The Role of Innovative Activity in An Active Economy (Eurasian Journal of History, Geography and Economics, 2022)
This article talks about the role of innovative activity in the active economy. The author characterizes the role of innovation in the development of modern civilization. Particular attention is paid to global statistics, thereby focusing on the factors that limit innovation activity in Uzbekistan. According to the author, it is intangible assets and intellectual capital that can provide maximum capitalization of the market value of enterprises, as well as attract additional sources of funds to finance innovation